Direct thrombin inhibitors, but not the direct factor Xa inhibitor rivaroxaban, increase tissue factor‐induced hypercoagulability in vitro and in vivo. (19th June 2014) - Perzborn, E.; Heitmeier, S.; Buetehorn, U.; Laux, V.
Summary Background Increased hypercoagulability has been reported with low doses of direct thrombin inhibitors but not with direct factor Xa inhibitors. Objectives To compare the effects of rivaroxaban with those of melagatran and dabigatran on thrombin generation (TG) and tissue factor‐induced hypercoagulability and to explore the possible involvement of the thrombin–thrombomodulin/activated protein C system. Methods In normal human plasma and in protein C‐deficient plasma, TG was investigated in vitro in the presence and absence of recombinant human soluble thrombomodulin (rhs‐TM). TG was determined by calibrated automated thrombography and an ELISA for prothrombin fragments 1+2 (F1+2). In an in vivo rat model, hypercoagulability was induced by tissue factor; levels of thrombin–antithrombin (TAT) and fibrinogen and the platelet count were determined. Results Rivaroxaban inhibited TG in a concentration‐dependent manner. In the absence of rhs‐TM, melagatran and dabigatran also inhibited TG concentration dependently. However, in the presence of rhs‐TM, lower concentrations of melagatran (119–474 nmol L–1) and dabigatran (68–545 nmol L−1) enhanced endogenous thrombin potential, peak TG, and F1+2 formation in normal plasma but not in protein C‐deficient plasma. In vivo, rivaroxaban dose‐dependently inhibited TAT generation, whereas melagatran showed a paradoxical effect, with an increase in TAT and a small decrease in fibrinogen and platelet count at lower doses. Conclusion Low concentrations of the direct thrombin inhibitors melagatran and dabigatran enhanced TG and hypercoagulability, possibly via inhibition of the protein C system. In contrast, rivaroxaban reduced TG and hypercoagulability under all conditions studied, suggesting that it does not suppress this negative‐feedback system.